2003
DOI: 10.1007/s00122-003-1272-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of QTLs for Fusarium head blight resistance in spring wheat. II. Resistance to fungal penetration and spread

Abstract: Fusarium head blight (FHB, scab) causes severe yield and quality losses, but the most serious concern is the mycotoxin contamination of cereal food and feed. The cultivation of resistant varieties may contribute to integrated control of this fungal disease. Breeding for FHB resistance by conventional selection is feasible, but tedious and expensive. The aim of this work was to detect QTLs for combined type I and type II resistance against FHB and estimate their effects in comparison to the QTLs identified prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
257
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(277 citation statements)
references
References 22 publications
17
257
0
3
Order By: Relevance
“…Molecular mapping provides a useful tool for characterization of the effect of quantitative trait loci (QTLs) for disease resistance, localization of the QTL on a chromosome region detected in a defined population, and understanding interactions between different disease resistance QTLs (Tanksley, 1993;Paterson, 1998). To date, several QTLs for FHB resistance have been reported (Bai & Shaner, 2004), and one QTL on chromosome 3BS from Sumai 3 and its derivative Ning7840 was consistently identified to have a major effect on FHB resistance in various genetic backgrounds (Bai et al, 1999;Anderson et al, 2001;Buerstmayr et al, 2002;Guo et al, 2003). Several types of DNA markers closely linked to the QTL have been identified (Bai et al, 1999;Waldron et al, 1999;Buerstmayr et al, 2002;Guo et al, 2003;Xu & Ban, 2004), and some of them have been extensively used for marker-assisted selection (MAS) in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mapping provides a useful tool for characterization of the effect of quantitative trait loci (QTLs) for disease resistance, localization of the QTL on a chromosome region detected in a defined population, and understanding interactions between different disease resistance QTLs (Tanksley, 1993;Paterson, 1998). To date, several QTLs for FHB resistance have been reported (Bai & Shaner, 2004), and one QTL on chromosome 3BS from Sumai 3 and its derivative Ning7840 was consistently identified to have a major effect on FHB resistance in various genetic backgrounds (Bai et al, 1999;Anderson et al, 2001;Buerstmayr et al, 2002;Guo et al, 2003). Several types of DNA markers closely linked to the QTL have been identified (Bai et al, 1999;Waldron et al, 1999;Buerstmayr et al, 2002;Guo et al, 2003;Xu & Ban, 2004), and some of them have been extensively used for marker-assisted selection (MAS) in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…It also has a higher probability of attack by insects, due to easiness of penetration in endosperm (Bútron et al, 2009). According to Buerstmayr et al (2003), the genetic resistance of the grain to the infection by Fusarium sp depends on two factors: resistance to the penetration of hyphae in the grain and resistance to the fungic development in endosperm of the grain. In a study carried out by Ono et al (2000) moldy grains have a positively correlation with the number of units of colony of Fusarium sp, indicating that grains with damages in pericarp is a way of fungi contamination.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained allele scores of the three polymorphic SNP markers were added to the pre-existing marker data for the CM-82036/Remus mapping population (Buerstmayr et al 2002(Buerstmayr et al , 2003 and/or the Frontana/ Remus population (Steiner et al 2004). The SNP markers were mapped using Mapmaker 3.0b (Lander et al 1987) with the commands 'group', 'order', 'try' and 'ripple'.…”
Section: Snp Detection and Mappingmentioning
confidence: 99%
“…'Frontana' shows a very complex resistance pattern that predominantly acts against fungal penetration, but also passive resistance associated with morphological features was found (Steiner et al 2004). On the other hand 'CM-82036' shows a very high level of resistance to fungal penetration and spread within the plants (Buerstmayr et al 2002(Buerstmayr et al , 2003. It has been shown that a major quantitative trait locus (QTL) for FHB resistance is linked to detoxiWcation of DON by glycosylation in CM-82036 (Lemmens et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation